2017
DOI: 10.1186/s13073-017-0418-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic pleiotropy between age-related macular degeneration and 16 complex diseases and traits

Abstract: BackgroundAge-related macular degeneration (AMD) is a common condition of vision loss with disease development strongly influenced by environmental and genetic factors. Recently, 34 loci were associated with AMD at genome-wide significance. So far, little is known about a genetic overlap between AMD and other complex diseases or disease-relevant traits.MethodsFor each of 60 complex diseases/traits with publicly available genome-wide significant association data, the lead genetic variant per independent locus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 119 publications
4
52
1
Order By: Relevance
“…Genetic pleiotropy between AMD and other complex diseases has been observed before. 39 The emerging question is, if there is such a commonality for these diseases in terms of their genetic makeup, what determines why one individual develops one and not all diseases? One reason may be that there are different polymorphisms in a single gene that create different risks for different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic pleiotropy between AMD and other complex diseases has been observed before. 39 The emerging question is, if there is such a commonality for these diseases in terms of their genetic makeup, what determines why one individual develops one and not all diseases? One reason may be that there are different polymorphisms in a single gene that create different risks for different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…More than 30 million individuals worldwide are affected by vision loss from AMD (6). Mutations in more than 20 genes and loci have been associated with increased risk of AMD (7,8). However, age and smoking remain the two highest risk factors, which suggests that oxidative stress and reactive oxygen species production play a pivotal role in early disease progression (8).…”
mentioning
confidence: 99%
“…Studies have shown that many traits are genetically correlated with each other 8 . Furthermore, studies have shown that hundreds of individual variants identified from GWA studies are associated with multiple traits [9][10][11][12][13][14] . Many of these variants for the most part have been used as IVs for causal inference in MR studies with the assumption that these variants do not have pleiotropic effects.…”
mentioning
confidence: 99%